Fin flat-plate type tetragon solar collector design based on convection radiation mechanism. Issue 1 (1st January 2019) - Wuryanti, Sri; Megawati,
Abstract: A solar collector that collects solar radiation from the sun is equipped with a heat absorber kit that can store heat for a long term. This system consists of collector box, acrylic-coated cover, black-coated-aluminum base, and finned absorber. The purpose of using the fin is to enlarge the surface area exposed to the sun's heat so that radiation heat transfer increases. This design is conducted for 460 W collector capacity, 1 m 2 surface area, expected output temperature between 60°C and 77°C. Flat-plate solar collector is used for heating the solar-energy-absorber plat. Furthermore, air is passed through the collector to become hot and flowed into the process room by using a fan. Tests are carried out four times, then the results for the lowest and highest output air temperature are 59°C and 77°C and the lowest and highest collector efficiency are 62% and 76%.